Owning the Code: Status Closure in Distributed Groups - Metiu, Anca (Organization Science, 2006)
An ethnographic study of a team of software developers working on a new product across two groups—located on the West Coast of the United States and in Bangalore, India—is used to analyze status dynamics in distributed groups. Whereas existing literature has emphasized the importance of communication, task design, and incentives for cooperation, this paper shows how status differentials and geographic distance reinforce each other to affect the work processes and collaboration in distributed teams. The focus is on two elements: the relationship between the collaboration across the two groups and their members and the members’ interpretations of this relationship. Status influences the perceptions of the remote group, as well as the willingness to cooperate with its members. The key findings specify the informal closure strategies used by the high-status group in relation to the low-status group. Furthermore, the superimposition of geographic and status distance in remote work lowered the cost of exclusion of one group from the collaboration and led to the deepening of status differences between remote groups. By showing status to be both an input and an output of intergroup relations, the paper specifies some of the mechanisms through which status orderings are maintained and reinforced.